Reduced ligninase‐cellulase ratio enhances soil carbon sequestration following afforestation of agricultural land - Shuhai Wen; Dailin Yu; Jiao Feng; Yu‐Rong Liu (Journal of Sustainable Agriculture and Environment)
Abstract Introduction Afforestation of agricultural land is one of the most essential approaches to mitigate climate change by enhancing the sequestration of atmospheric carbon (C) into the soil. C‐degrading extracellular enzymes produced by soil microbes regulated the decomposition and fate of sequestrated soil organic carbon (SOC), with potential divergent variations following afforestation across different ecosystem scales. However, the feedbacks of different C‐degrading enzymes and their relationships with SOC following afforestation of agricultural land remain unclear. Materials and Methods We investigated the changes in enzyme activity and their relationships with SOC in soil aggregates across two typical climatic vegetation restoration regions in China, and explored the mechanisms through which changes in enzyme activity contribute to SOC sequestration following afforestation of agricultural land. Results Afforestation of agricultural land generally decreased ligninase activity and increased cellulase activity across various aggregate fractions, compared to the adjacent croplands in both subtropic (Danjiangkou Reservoir, DJK) and temperate (Maoershan, MES) region. Additionally, the ratio of ligninase to cellulase (L:C) was lower in afforested lands than in the croplands, with L:C as the major factor explaining the variations of SOC sequestration following afforestation. Specifically, ligninase and L:C were negatively correlated with SOC, whereas cellulase showed positive correlations with SOC. Further analyses suggested that microbial biomass C and nitrogen (MBC and MBN) and the ratio of SOC and total nitrogen (SOC:TN) were important factors influencing L:C and subsequently regulating SOC. These results suggest that shifts in microbial enzyme production from ligninase to cellulase following afforestation, reduced the decomposition of recalcitrant C, thus contributing to SOC sequestration. Conclusion Our work underscores the critical role of reduced L:C in enhancing SOC sequestration following the restoration of croplands to afforested lands. These findings advance the understanding of the influence of microbial community physiological adaptations on C sequestration across different land use types.